ANALISIS KEWAJIBAN PPH 21, 23 DAN 4 AYAT 2 PT NICK 2020 - Weslyn, Renny; Widjaja, Purnamawati Helen (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This research aims to find out how the NICK company which is engaged in cold storage rental has carried out its tax obligations as stipulated in the current tax regulations in Indonesia. This study was also conducted to test compliance with the deposit and reporting of PT NICK's Tax Period Tax Return on these three tax aspects in fulfilling their tax obligations as corporate taxpayers. This study uses a qualitative method. Qualitative methods are research methods based on post-positivity, which are used to study the state of natural objects where researchers will use them as key instruments, data collection techniques that are carried out in a combined manner. This type of research uses descriptive research and the data sources used are secondary data and primary data. The results of this study indicate that PT NICK has carried out its tax obligations on these three aspects and is in accordance with the applicable tax regulations. The three aspects of taxation include PPh 21, PPh 23 and PPh 4 paragraph 2. However, it appears that PT NICK's calculations and withholdings have been found to have underpaid income tax article 21 from January to December 2020.